Hubungan Pediculosis Capitis dengan Tingkat Konsentrasi pada Murid Kelas V SD Qoshrul Muhajirin Singaparna - Harisha Auliya Yasyfa; Ismawati (UNISBA Press, 2023)
Pediculosis capitis is a scalp disease caused by an infestation of mites/lice of the Pediculus humanus capitis species which is an ectoparasite in humans. Pediculosis capitis infestation often occurs in elementary school-age children. In children, the symptoms obtained from head lice bites can cause irritation, sores and infection if scratched intensively so that it can interfere with children's learning concentration. This study aims to determine the relationship between Pediculosis capitis and the level of learning concentration in fifth grade students conducted at SD Qoshrul Muhajirin Singaparna. The number of samples taken was 47 people using simple random sampling technique. The type of research used is analytic observational with a cross sectional approach. Assessment of the level of learning concentration in students is measured using the stroop test. The results of the stroop test showed that 44 students had an interference score > 13, which means bad. After statistical analysis using the chi-square method, it was found that the value of p = 0.198 (p> 0.05), which means that there is no relationship between Pediculosis capitis and learning concentration in fifth grade students at SD Qoshrul Muhajirin Singaparna. The conclusion of this study showed that the concentration level was not affected by Pediculosis capitis infestation. Factors that may affect the results of this inconsistent research are caused by the use of the stroop test which is difficult for elementary students to carry out and other factors such as the phase of head lice and the environment. Pediculosis capitis adalah penyakit kulit kepala akibat infestasi tungau/lice spesies yang merupakan ektoparasit pada manusia. Infestasi Pediculosis capitis terjadi sering pada anak usia sekolah dasar. Di Indonesia diperkirakan 15% anak usia belajar yang mengalami Pediculosis capitis. Gejala dari gigitan kutu kepala pada anak yaitu iritasi, luka serta infeksi sekunder jika menggaruk secara intensif sehingga mengganggu konsentrasi anak. Penelitian ini bertujuan untuk mengetahui hubungan Pediculosis capitis dengan tingkat konsentrasi pada murid kelas V yang dilakukan di SD Qoshrul Muhajirin Singaparna. Jenis penelitian yang digunakan adalah observasional analitik dengan pendekatan potong lintang. Jumlah sampel yang diambil yaitu 47 responden dengan menggunakan teknik simple random sampling. Penilaian tingkat konsentrasi murid diukur menggunakan stroop test. Hasil penelitian stroop test menunjukan 44 murid memiliki nilai interference score >13 yang berarti buruk. Setelah dilakukan analisis statistik menggunakan metode chi-square didapatkan nilai p=0,198 (p>0,05) yang berarti tidak terdapat hubungan Pediculosis capitis dengan konsentrasi pada murid kelas V SD Qoshrul Muhajirin Singaparna. Kesimpulan penelitian ini menunjukan bahwa tingkat konsentrasi tidak dipengaruhi oleh infestasi Pediculosis capitis. Faktor yang dapat mempengaruhi hasil dari penelitian yang tidak sejalan ini yaitu disebabkan oleh penggunaan stroop test yang sulit dilakukan oleh murid SD dan faktor lain seperti fase dari kutu kepala dan lingkungan.